Ratification of the United Nations Convention on the Rights of Persons with Disabilities: Implication and Reality From A Legal Dimension and Equality of Rights: (Ratifikasi Konvensyen Pertubuhan Bangsa-Bangsa Bersatu terhadap Hak Orang Kurang Upaya: Implikasi dan Realiti dari Dimensi Perundangan dan Kesamarataan) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Issues related to the disabled right in the country continue to attract criticism and debate, as implementation is very slow and weak. The disabled have the right to live like other normal people, which includes protection in times of danger and emergency. One of the important mechanism for the care of the disabled is through legal means. The government has signed the United Nations Convention on the Rights of Persons with Disabilities (CRPD) as part of its efforts to empower and protect this minority group. As such, the government has taken the initiative to enact the Persons with Disabilities Act 2008 and ratified the Convention on the Rights of Persons with Disabilities (CRPD) in 2010 as one of the government's commitments in complying with international human rights conventions as long these do not against the Federal Constitution. This article aims to uncover and analyse the legal provisions in Malaysia relating to the disabled and their right to live, as stated in the Federal Constitution and relevant legal provisions. In essence, this shows that Malaysia, as a member of the UN, is bound to adopt international laws and treaties on human rights if these do not violate local norms and values. At the end of the discussion, some ideas are presented as solutions for the government to improve the issue of disabled persons so that in the eyes of the world, Malaysia will be recognized as one of the countries that cares for and defends its disabled, in line with the Convention on the Rights of Persons with Disabilities 2008.Keywords: Ratification, Convention on the Rights of Persons with Disabilities 2008 (CRPD), Equality, International human rights, Malaysian Laws